2021
DOI: 10.1177/2374373521997733
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Structured Clinical Handover Protocol on Communication and Patient Satisfaction

Abstract: The Handover process is an essential aspect of patient care in daily clinical practice to ensure continuity of patient care. Standardization of clinical handover may reduce sentinel events due to inaccurate and ineffective communication. Single arm experimental trial was conducted to assess the effect of standard Situation, Background, Assessment, Recommendation (SBAR) protocol implementation in overall bedside nursing handover process, patient satisfaction, and nurses’ acceptance. As a sample, all nursing sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 17 publications
1
14
0
5
Order By: Relevance
“…Only a correct cognitive system can ensure that patients consciously practice correct and scientific behaviors, thereby reducing the incidence of adverse events, avoiding risk factors, and making them face the disease with a more peaceful mind. The traditional cognitive intervention model has not yet started from the patient's subjective level, and more is to provide patients with passive theoretical knowledge points, which cannot ensure that patients can better internalize and absorb relevant knowledge content ( 17 ). Under this opportunity, we started from the patients’ closest relatives to provide them with appropriate clinical diagnosis and care, so as to ensure the holistic prognosis and outcome of the patient's condition.…”
Section: Discussionmentioning
confidence: 99%
“…Only a correct cognitive system can ensure that patients consciously practice correct and scientific behaviors, thereby reducing the incidence of adverse events, avoiding risk factors, and making them face the disease with a more peaceful mind. The traditional cognitive intervention model has not yet started from the patient's subjective level, and more is to provide patients with passive theoretical knowledge points, which cannot ensure that patients can better internalize and absorb relevant knowledge content ( 17 ). Under this opportunity, we started from the patients’ closest relatives to provide them with appropriate clinical diagnosis and care, so as to ensure the holistic prognosis and outcome of the patient's condition.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the doctors in this survey were comfortable with adding the SBAR form as a tool for handoff communication, while Nagammal et al reported that only 1% of the nurses had poor satisfaction regarding using the SBAR form [17]. Furthermore, previous literature indicates that using communication tools like SBAR does not consume time or effort to complete, helps in the efficient delivery of patients' information, encourages healthcare professionals' collaboration, and decreases the rate of miscommunication errors [13,[19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Nursing handover is a major determinant of the quality of patient care in the critical care unit. The goal of clinical handover is to ensure continuity of care and informed clinical decision making as guided by the patient condition (Ghosh et al, 2021). Nursing handover occur during a shift change within one unit or at times from one unit to another when patients are transferred in and out of the critical care unit (Loefgren Vretare & Anderzén-Carlsson, 2020).…”
Section: Problem Statementmentioning
confidence: 99%
“…The findings also state that a joint focus of attention facilitates the two team in handover to coordinate their visual and verbal attention. In another study conducted by Ghosh et al, (2021) using a mixed method design to compare nurse satisfaction before and after introduction of a structured communication tool, it was found that it led to positive evidence based behaviors during handover. In an integrative review of literature to identify the factors that should be deliberated when evaluating bedside handover, the crucial components of communication were noted to be: succinctness of information, clarity of information, volume of information and respectful listening (Forde et al, 2018).…”
Section: Enablers Of Nursing Handovermentioning
confidence: 99%